Unravelling interspecific relationships among highland lizards : first phylogenetic hypothesis using total evidence of the Liolaemus montanus group (Iguania: Liolaemidae) - Abdala, Cristian Simón (2020)
Fil: Abdala, Cristian Simón. Consejo Nacional de Investigación Científicas y Técnicas. Unidad ejecutora Lillo Tucumán; Argentina.